Love in the Time of War: Identifying Neighborhood-level Predictors of Intimate Partner Violence from a Longitudinal Study in Refugee-hosting Communities - Treves-Kagan, Sarah (Journal of interpersonal violence, 2022)
A high prevalence of intimate partner violence (IPV) has been documented among women living in conflict-affected and refugee-hosting areas, but why this occurs is not well understood. Conflict and displacement deteriorate communities? social cohesion and community connectedness; these neighborhood social environments may influence individual IPV outcomes. We explored neighborhood-level social disorganization and cohesion as predictors of recent IPV in refugee-hosting communities in northern Ecuador by conducting multi-level logistic regression on a longitudinal sample of 1,312 women. Neighborhood social disorganization was marginally positively associated with emotional IPV (AOR: 1.17, 95% CI: .99, 1.38) and physical and/or sexual IPV (AOR: 1.20, 95% CI: .96, 1.51). This was partially mediated by neighborhood-level civic engagement in the case of emotional IPV. At the household level, perceived discrimination and experience of psychosocial stressors were risk factors for both types of IPV, whereas social support was protective. To our knowledge, this is one of the first studies to examine how neighborhood social factors influence IPV outcomes in refugee-hosting communities or in South America. As the world grapples with the largest number of displaced people in history, this research can inform prevention and response programming and reinforces the critical importance of promoting acceptance of refugees and immigrants and positively engaging all community members in civic life in refugee-hosting settings.